Blindness and low vision in a tertiary ophthalmologic center in Thailand: The importance of cytomegalovirus retinitis - Kessara Pathanapitoon (2018)
PURPOSE: To determine the causes of blindness and low vision in patients consulting a tertiary ophthalmologic center in northern Thailand. METHODS: The study population included 2,951 new consecutive patients from the Department of Ophthalmology at University Hospital in Chiang-Mai, Thailand. Main outcome measures were blindness and low vision, which were defined according to World Health Organization criteria. RESULTS: Of 2,951 patients, 369 (12.5%) had blindness and/or low vision (bilateral blindness in 73, unilateral blindness in 129, bilateral low vision in 77, and unilateral low vision in 90). Of the etiological causes of visual loss, age-related ocular disease was the most frequent (128 patients [35%]) followed by infections (66 patients [18%]) and trauma (43 patients [12%]). Although infections and trauma were the predominant causes of blindness, age-related disorders were frequently found in patients with low vision. Of anatomical sites, the lens (134 patients [36%]) was the main location of visual loss, closely followed by disorders of the retina and/or uvea (126 patients [34%]). Blindness and low vision were considered avoidable in 70% of cases. Of 73 patients with bilateral blindness, 14 had active cytomegalovirus retinitis, accounting for 19% of all patients with bilateral blindness. CONCLUSION: The most common causes of blindness and low vision in a tertiary center in northern Thailand were age-related ocular disorders and infections, which were predominantly cases of cytomegalovirus retinitis in human immunodeficiency virus-infected patients. © The Ophthalmic Communications Society, Inc.